Strength of Slotted Stainless Steel Tubular Member Tension Connections - Kıymaz, Güven; SEÇKİN, EDİP (My University, 2010)
In the present study, shear lag induced failure of slotted end tension connections is considered for circular hollow section members in stainless steel. The failure of slotted end tension connections is mostly governed by fracture near the slotted end where local peak stress concentrations develop due to shear lag. Within the connected region, shear lag causes the unconnected circumferential region of the hollow section to lag behind the welded region in resisting the axial tensile forces. An experimental program carried out on 10 slotted gusset plate welded stainless steel circular member end connections is first described. The results obtained from the test program are critically examined and compared with currently available design guidance for slotted gusset plate welded tubular end connections. It is noted that no specific rules exist in international specifications on structural stainless steel which cover the design of such connections. Therefore, the results of this study are compared with the design rules for carbon steel. It is suggested that present requirements for such connections in carbon steel may be different if applied to stainless steels.
Keywords: stainless steel; slotted circular hollow section; square hollow section